PC-based aviation training devices (PCATDs): research, development and certification - Reweti, Savern; Gilbey, Andrew; Jeffreys, L; Hall, S (Massey University, 2011)
This paper examines the development of two PCATD’s (one helicopter, one fixed-wing) and their eventual certification by CAA. Certification has demonstrated the potential these devices have for aviation training in New Zealand. Traditionally FTD‘s and PCATD’s have been sourced from foreign companies, and they represent a considerable financial investment for large flying training organisations. The procurement of these simulator types is generally beyond the financial resources of most small to medium sized flying schools. Aviation training in NZ is facing significant financial constraints as well as an increasing demand to simulate complex glass cockpit systems that are now installed in most new General Aviation (GA) aircraft. The development, utilisation and certification of this type of PCATD technology could solve these difficult challenges.
Keywords: Aviation; Simulation; PC-Based ATD; Software; Pilot training; Massey University